Data-Driven Policy Making and Its Impacts on Regulation: A Study of the OECD Vision in the Light of Data Critical Studies - Clarissa Valli Buttow; Herwig C.H. Hofmann; Felix Pflücke (European Journal of Risk Regulation)
While the private sector is leading the way in digital transformation, the public sector is perceived as missing the opportunity. The way forward in this transformation is pointed out as adopting data-driven technologies as drivers of public policies. This will undoubtedly transform the regulatory process. To better understand how these technologies would intervene in the policy cycle and the effect of this transformation on regulation, this paper studies the work of the Organisation for Economic Co-operation and Development on the matter. Adopting the public policy cycle as an analytical lens and illuminated by the insights of Critical Data Studies, this paper deepens the understanding of how these technologies could change the policy cycle and bring together steps previously conceived as subsequential stages. This transformation can trigger a real disruption of the regulatory process as we currently know it.